Brachet-Márquez, Viviane y Uribe Gómez, Mónica (coords.). (2016). Estado y sociedad en América Latina. Acercamientos relacionales. México, D. F.: El Colegio de México. - Vélez Rendón, Juan Carlos (Estudios Políticos, 2018)
.